2013
DOI: 10.1111/aab.12036
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oxidative stress caused by NaCl or Na2SO4 excess on lipoic acid and tocopherols in Genovese and Fine basil (Ocimum basilicum)

Abstract: With this investigation, we aimed to study more deeply the antioxidative response to moderate doses of NaCl or Na 2 SO 4 in two cultivars of basil differentially sensitive to salinity. Tolerance to salinity was previously evaluated by the extent of growth inhibition whereas the antioxidant response was assessed studying the changes in the activities of superoxide dismutase (SOD) and catalase as well as in the amounts of tocopherols and lipoic acid. To make possible the comparison of the responses of basil cv. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
4
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 38 publications
(59 reference statements)
1
16
4
2
Order By: Relevance
“…Previous studies have provided evidence that, in animals, LA application restored reduced levels of the antioxidant substances such as AsA and GSH . Up to date, only a few studies have been reported exhibiting the relationship between endogenous levels of LA/DHLA and the other antioxidant substances in plants . We found that salt stress had an important effect on the contents of total AsA and GSH, and levels of their reduced (AsA and GSH) and oxidised (DHA and GSSG) forms.…”
Section: Discussionmentioning
confidence: 47%
“…Previous studies have provided evidence that, in animals, LA application restored reduced levels of the antioxidant substances such as AsA and GSH . Up to date, only a few studies have been reported exhibiting the relationship between endogenous levels of LA/DHLA and the other antioxidant substances in plants . We found that salt stress had an important effect on the contents of total AsA and GSH, and levels of their reduced (AsA and GSH) and oxidised (DHA and GSSG) forms.…”
Section: Discussionmentioning
confidence: 47%
“…This tolerance has been earlier attributed to a smaller leaf biomass combined with reduced stomatal density , both of which would contribute to reduced transpiration under saline stress (James et al, 2002). Salt stress tolerance of GEN plants was also documented by Tarchoune et al (2013), who reported no change in shoot fresh weight after 15 days of 50 mM NaCl treatment. The reduction of leaf area, along with the decrease of SLA in salt-treated plants was already visible in the first stages of stress at 13 DAST (Table 1), confirming that the reduction of cell expansion and cell division is an early response to salt stress (Munns, 2002;Ruggiero et al, 2004).…”
Section: Plant Growth Under Salt Stressmentioning
confidence: 76%
“…Similar amounts of a-tocopherol in C. spinosum have been reported by Vardavas et al (2006), although they also detected c-tocopherol which was not the case in our study. Moreover, Tarchoune et al (2013) reported that tocopherol biosynthesis under stressful conditions is involved in mechanisms responsible for the detoxification of ROS in mildly salt tolerant species such as basil.…”
mentioning
confidence: 99%